THE CONTENT OF COMPOUND AND BIOACTIVE SUBSTANCE OF THE ROSELLA PETALS EXTRACT GEL TO ACCELERATE THE REMODELING PROCESS OF THE ALVEOLAR BONE - UTAMA, MOHAMMAD DHARMA; AMIRUDDIN, MAQHFIRAH; ARPA, SITTI; ASSE, RUSTAN AMBO; IKHRIAHNI; MUCHTAR, MERIYAM; SUSANIAWATY, YULI (International Journal of Applied Pharmaceutics, 2019)
Objective: One of the many natural plants that are used as a remedy for the body is the Rosella Flower (Hibiscus Sabdariffa). Rosella Flowers have been widely known to have many useful compounds such as calcium and other bioactive substances in which bone tissue. Methods: The research using laboratory experimental method, with gel making of 10% Rosella Petals Extract which then destructed and decomposed in order to see the contents of compound and bioactive substances and its value contained in 10% Rosella Petals Extract Gel, Afterward, the gel was inserted into the socket at the time of dental implant insertion and subsequent bone remodeling process was observed within 14, 28 and 56 d intervals, then analyzed to see the levels of compound and bioactive substance. Results: The extract content of Rosella Petals and 10% Rosella Petals Extract Gel had significant value of Protein, Vitamin C, Beta Carotene, and Calcium, as evidenced by the Rosella Petals Gel added at the time of dental implant insertion, the result obtained after examination of bone tissue formation at days 14, 28, and 56 levels of calcium increased compared with the control group that did not use addition of Rosella Petal Extract Gel. Conclusion: 10% Rosella Petals Extract Gel contains a composition that can accelerate the remodeling process of the alveolar bone.